How does the immunogenicity of hepatitis B vaccine change over the years in childhood? - Gulsum Iclal Bayhan; Sidika Elif Balli; Hatice Demir; Zekiye Baydar (Taylor & Francis Group, 2021)
Hepatitis B is the leading cause of chronic hepatitis, cirrhosis, and hepatocellular carcinoma worldwide. The incidence of HBV infection has significantly decreased with hepatitis B vaccination. Hepatitis B vaccine is administered to children at 0, 1 and 6 months of age according to the national schedule. There is a high rate of protective antibody (anti-HBs) development after hepatitis B vaccination. We conducted the study to investigate how the hepatitis B surface antibody (anti-HBs) positivity rates and the titers change over time in childhood following vaccination. Patients who presented at the general pediatric outpatient clinic of Yenimahalle Education and Training Hospital and the HBsAg and anti-HBs titers were tested for any reason between July 2011 and May 2018 were retrospectively evaluated. The cutoff level for protection by the anti-HBs titer was accepted as ≥10 mIU/mL with lower levels indicating no protection. Anti-HBs positivity was compared by age group. Anti-HBs levels were studied in 4326 children. The mean age of the included in the study was 127 ± 62 months. A protective anti-HBs level (≥10 mIU/mL) was present in 2292 children (69.2%). The highest anti-HBs antibody positivity rate was in the under 3 years' age group. The positivity rate significantly decreased after age 7 years. The HBsAg level was determined in all children in the study and five had a positive result. In conclusion, our study found that the anti-HBs positivity rate and the anti-HBs level decreased with age. However, the anti-HBs antibody result remained positive in more than half of the children.